DEVELOPMENT OF A SOFTWARE PROTOTYPE BASED ON THE HEALTH BOOKLET OF THE ELDERLY PERSON - Cássia Evangelista Delgado; Fernanda Matoso Siqueira; Grace Kelly Silva de Freitas; Dárlinton Barbosa Feres Carvalho; Fabíola Lisboa da Silveira Fortes; Ricardo Bezerra Cavalcante (Universidade Federal do Paraná, 2023)
Objective: to describe the development of a software prototype based on the Health Booklet for the Elderly, using Heuristic Evaluation to analyze its usability. Method: applied technological development research, using Nielsen's Heuristic Evaluation as a way of carrying out usability analysis, which began in November 2021 in Juiz de Fora and São João Del Rei. Results: the initial prototype has 5 screens, which contain some relevant data for the health care of the elderly, such as age, comorbidities, and history of allergies. The elderly will be able to edit their personal data, but only professionals will be able to include the patient's health data, with the aim of making it more reliable.  Conclusion: The use of this application will help to update and advance the use of technologies aimed at health care and will bring benefits to health systems and users.